Cervical CT-Guided, Selective Nerve Root Blocks: Improved Safety by Dorsal Approach - Wolter, T.; Mohadjer, M.; Berlis, A.; Knoeller, S. (American Journal of Neuroradiology, 2009)
SUMMARY: Cervical transforaminal blocks are frequently performed as a treatment of cervical radicular pain. These blocks are performed mostly under fluoroscopy, but a CT-guided technique also has been described. We describe a modification that leads to a more extraforaminal than transforaminal and equally selective nerve root block.